Industrial Relations Mediation in Cases of Termination of Employment by Employers: A Study at the Aceh Department of Labor and Population Mobility - Mahliga Nurmayani; Sanusi Sanusi; Zainal Abidin (International Journal of Law, Crime and Justice, 2026)
Termination of employment by employers often gives rise to industrial relations disputes, which are resolved through mediation as stipulated in Law No. 2 of 2004 on the Settlement of Industrial Relations Disputes. However, the implementation of mediation has not yet been fully effective in resolving disputes. This study aims to analyze the legal framework of industrial relations mediation in the resolution of termination disputes, assess the effectiveness of its implementation at the Aceh Department of Manpower and Population Mobility, and identify the obstacles and solutions encountered. This study is an empirical legal study employing legislative, conceptual, and case-based approaches. Data were collected through a literature review and field research via interviews with industrial relations mediators, officials from the Aceh Department of Manpower and Population Mobility, and legal practitioners, supported by documents related to the resolution of industrial relations disputes. The data were analyzed qualitatively. The results indicate that the legal framework for industrial relations mediation is adequate, but its implementation has not been effective. During the 2023–2025 period, 37 layoff cases were mediated, but only 6 cases were successfully resolved through a Joint Agreement, while the remaining cases ended with the mediator’s recommendation or were referred to the Industrial Relations Court. The low effectiveness of mediation is influenced by a lack of good faith on the part of the parties, an imbalance in bargaining power between workers and employers, the weak binding nature of the mediator’s recommendations, and the parties’ limited legal understanding. Therefore, it is necessary to strengthen the capacity of mediators, increase the parties’ legal awareness, and improve regulations to enhance the effectiveness of resolving industrial relations disputes through mediation.